Children and youth in the institutional setting – mental health characteristics of children from the Center for Protection of Infants, Children, and Youth in Belgrade - Milosavljević-Djukić, Ivana (Vojnosanitetski pregled, 2022)
Background/Aim. Unfavorable life experiences of children and youth, unmet emotional needs at an early age may lead to difficulties in emotional life and mental health or externalizing problems. The aim of the study was to determine the number of children in the Center for Protection of Infants, Children, and Youth (hereinafter Center) in Belgrade with mental health issues, their life circumstances, and the way their issues are manifesting. Methods. The study included all children in residence (n = 486) at the Center during 2015. The study was conducted in the period from February to April 2016. For the needs of the research, a questionnaire examining the children's mental health issues was developed. Both health workers and social workers participated in the research. The children's health status questionnaire was filled in from their health records, while social anamnestic data were taken from the social worker's records. The research included four group homes for children without parental care, ages between 7 and 18 years, 3 children's shelters for children from birth to 18 years, and the organizational unit infirmary (children with developmental difficulties, aged between 4 and 18 years). Results. Out of the total number of children placed in institutions during 2015 (n = 486), 96 (19.8%) children were diagnosed with mental health issues. The most frequent diagnoses were F90-F93 (behavioral and emotional disorders usually occurring in childhood and adolescence); F70-F72 (mental retardation); F30-F32.3 (mood disorder –affective disorder). The percentage of children with mental health issues diagnosed prior to their admission was 41.7% with one diagnosis, while 21.8% had two, three, or more diagnoses. After being received to the institution, 36.5% of children and youth got their diagnosis. Prior to their arrival at the Center, 74% of children had more than one life change. The average age of children was 11 years, although there were deviations in two group homes (15 years). After the paramedic emergency intervention, 21% of children were hospitalized. Inadequate parental care was the most prominent reason for institutionalization into the organizational units of children's homes, as well as the inability of parents to exercise their parental rights (76%). Inadequate parental care was neglected in 2/3 of children, while in 1/3 of children, it was abuse. Conclusion. Living in an institutional setting can lead to a number of problems in child development. The results of the research unequivocally show that children and adolescents placed in the social protection system are a vulnerable population and at a significantly higher risk of developing mental disorders, considering the negative influences and the absence of positive emotional stimuli from the earliest childhood. The type of consequence due to the stay at the institution depends on the age of the child, the length of the stay, their previous family experience, and the life changes that the child had.
Keywords: adolescent; child; mental disorders; mental health; psychology, social; risk assessment.